2018
DOI: 10.1155/2018/4914358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Routine Microscopy Performance for Malaria Diagnosis at Three Different Health Centers in Brazzaville, Republic of Congo

Abstract: Background In Republic of Congo, malaria diagnosis still widely relies on microscopy. We aimed to evaluate the performance of routine microscopy for malaria diagnosis at three different health centers in Brazzaville. Methods A total of 259, 416, and 131 patients with clinical signs of uncomplicated malaria were enrolled at the Hôpital de Mfilou, Centre de Santé Intégré “Maman Mboualé,” and Laboratoire National de Santé Publique, respectively. Two thick blood smears were prepared for each patient, the first bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…This result was lower than the ndings reported from other parts of Ethiopia [22], [23] [25] and, similar ndings were also reported in Pakistan [26]. However, our nding was in line with a study performed in the Democratic Republic of Congo which showed the performance of routine malaria microscopy remains inaccurate with large variations among different health centers [27]. Accurate microscopy results depend on the availability of a competent microscopist using good-quality reagents for examining well-prepared slides and with a low-to-moderate workload [21].…”
Section: Discussionsupporting
confidence: 74%
“…This result was lower than the ndings reported from other parts of Ethiopia [22], [23] [25] and, similar ndings were also reported in Pakistan [26]. However, our nding was in line with a study performed in the Democratic Republic of Congo which showed the performance of routine malaria microscopy remains inaccurate with large variations among different health centers [27]. Accurate microscopy results depend on the availability of a competent microscopist using good-quality reagents for examining well-prepared slides and with a low-to-moderate workload [21].…”
Section: Discussionsupporting
confidence: 74%
“…The high inter-microscopist concordance in parasite speciation and parasite density estimation in our study highlights the importance of intense training before TES initiation because there is often high variation in microscopy readings in routine malaria diagnosis laboratories. 38,39 This high concordance was probably because of the quality of laboratory training given to study microscopists because, like in most of the Americas, this study took place in an area with transmission of both P. vivax and P. falciparum. We also interacted often with the laboratory staff of the health facilities that served as enrollment sites and staff at the regional reference laboratory.…”
Section: Discussionmentioning
confidence: 88%
“…The study was conducted in Brazzaville, the political capital hosting 38% (1 642 105 inhabitants) of the total population of the Republic of Congo, estimated at 4 312 715 inhabitants as described elsewhere [20,21]. Due to the fluctuation of malaria transmission in Brazzaville, which varies from low, moderate to intense with meso-, hyper-to perennial endemicity, three different centers were considered for patients recruitment: Centre de Santé Intégré (CSI) « Maman Mboualé» located in the north part of city (4°13'S, 15°17'E); Hôpital de Mfilou located in the south part of the city (4°15'S, 15°13'E) and the Laboratoire National de Santé Publique (LNSP) located in the center part of city (4°16'S, 15°15'E).…”
Section: Study Areasmentioning
confidence: 99%
“…Exclusion criteria were pregnancy, severe malaria or other severe illness as judged by the attending physician. The number of representative patients to be included in each site was estimated taking into account the proportion of malaria reported in each health center, one year before starting the study as described elsewhere [20,21].Thus, 310, 200 and 100 were a minimum number of patients to be recruited at the CSI « Maman Mboualé», Hôpital de Mfilou and the LNSP, respectively. After informed consent was obtained, records were made on patient demographics, fever or history of fever in the last 48 hours, other signs of malaria, provenance, previous antimalarial drugs intake, and insecticide treated nets.…”
Section: Study Population Blood Samples and Data Collectionmentioning
confidence: 99%